2019
DOI: 10.1186/s12889-019-7381-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health literacy in the general population: results of the Catalan health survey

Abstract: Background Health Literacy (HL) is the knowledge and competence to access, understand, appraise, and apply health information for health judgment. We analyze for the first time HL level of Catalonia’s population. Our objective was to assess HL of population in our area and to identify social determinants of HL in order to improve the strategies of the Healthcare Plan, aimed at establishing a person-centered system and reducing social inequalities in health. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
81
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 27 publications
8
81
4
2
Order By: Relevance
“…The frequency of limited HL in Polish society was much higher than among respondents from Catalonia as reported in a recent study by Garcia-Codina et al [29]. They performed a survey of HL on a group of 2433 inhabitants [27].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The frequency of limited HL in Polish society was much higher than among respondents from Catalonia as reported in a recent study by Garcia-Codina et al [29]. They performed a survey of HL on a group of 2433 inhabitants [27].…”
Section: Discussionmentioning
confidence: 77%
“…Other studies, in which national versions of the HL questionnaire developed within the HLS-EU project were used, confirmed that low HL may be associated with people's poor self-assessment of health status [12,20], the prevalence of long-term illnesses [12], the higher utilisation of health care resources [14,21], and a lower level of physical activity [22][23][24].Although the scope of information which arises from the HLS-EU-Q47 is extensive, it appears that the size of the tool may result in reduced compliance of respondents, especially if the questionnaire is used as a part of a survey which is also focused on other issues. Therefore, a shortened but also validated, the 16-item version has been used in many surveys (HLS-EU-Q16) [5,12,[25][26][27][28][29]. The HLS-EU-Q16 questionnaire has been used not only in direct interviews with respondents [27,29] but also for telephone-based studies [12,26,30] or online surveys [31].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(15,16) Variations in general health literacy have been linked to multiple determinants ranging from education to socioeconomic statuses. (17) Likewise, this is expected for pandemic related health literacy.…”
Section: Introductionmentioning
confidence: 99%